Management Information System for Achieving Main Performance Indicators for Higher Education - Mewengkang, Alfrina; Sumual, Herry; Podung, Beatrix J.; Wullur, Mozes M. (JR Education, 2024)
The aim of this research is to develop a management information system for the achievement of Main Performance Indicators (MPI) for universities in Indonesia, especially the achievement of indicators for Students Gaining Experience Outside the University Campus and to be able to monitor the performance achievements of each study program in accordance with performance targets, especially at Universitas Negeri Manado (Unima). The development of this management information system uses the Extreme Programming Method which consists of Planning, Design, Coding and Testing. The result of this research is the Unima MPI Achievement Management Information System, which can be used by universities to input and report the performance achievements of each study program. From the research results, this Management Information System helps in: 1) planning the achievement of MPI by providing the data and information needed to formulate appropriate goals, strategies and action plans 2) in organizing the process of achieving MPI by managing the flow of information, tasks and responsibilities responsibilities between main actors such as students, admin, study program and rector; 3) facilitate the implementation of the achievement of main performance indicators by providing appropriate access to each actor to enter, verify and view data on the achievement of main performance indicators and 4) Management information systems play an important role in controlling the achievement of MPI by providing appropriate access control and regulation and provide the information necessary to evaluate the successful implementation of educational policies and programs. With the Management Information System for Achieving Main Performance Indicators, educational institutions can plan, organize, implement and control the achievement of main performance indicators effectively and efficiently in accordance with the performance targets that have been set by the Indonesian Ministry of Education, Culture, Research and Technology.